Maecenas, the last etruscan (Iter, 2022)
Cussen is the author ofa book of verseswhere he introduces Maecenas, the renowned counselor andfriendof Augustus*, dictating some poem-letters for Virgil and the emperor tohis secretary. In them Rome lives the splendor o f its glory and thetiredness ofits decline, and the characters discover the depth ofits soulwithin the framework ofa historical happening devoid of melancholy.